(untitled) (Journal of Plant Disease Sciences, 2020)
Potato is the most important root and tuber crop in sub-tropical and tropical areas where it is a primary staple food in many of the poorest countries. Root-knot nematodes are lethal plant-parasitic nematodes from the genus Meloidogyne and prefer warm soil conditions for their life. The root knot nematode, Meloidogyne incognita, is an obligate parasite that causes significant global crop loss and damage to a broad range of host plants by disturbing the physiological process of photosynthesis and nutrient uptake. Among thousands of plant hosts this microscopic roundworm invades roots and later tubers, establish feeding sites, and develop into the adult stage in potato food crop. The presence of RKN in this crop becomes one of the major problems nowadays because they cause great potato tuber yield loss. This review discussed on geographical distribution, Life cycle, symptoms on potatoes, sampling and identification, economic impact, and management approaches of M. incognita nematode species in potato production. The major problem caused by this nematode species is transmission of tobacco rattle virus, which causes corky ringspot disease on developing tubers.